Sport Events as City Branding Strategies: A Case Study of the 2022 Hangzhou Asian Games - Zhang, Zilin; Sha, Mingqiu; Wang, Zirui; Bao, Yifan (International Journal of Social Sciences and Public Administration, 2025)
In the post-pandemic era, host cities are increasingly utilizing sports events as strategic tools to enhance brand identity, stimulate urban development, and drive economic recovery. This paper investigates the 2022 Hangzhou Asian Games as a case study in city branding, analyzing the effectiveness of two strategies: cost-efficient infrastructure development and the integration of cultural heritage with innovative technology. Through content and stakeholder analyses, the research discusses the Hangzhou Asian Games’ impact on various stakeholders, highlighting the holistic socioeconomic effects and global applicability of such events. The results suggest that leveraging existing infrastructure and empowering local businesses enhanced both cost efficiency and maximized benefits. Additionally, by integrating traditional culture with advanced technologies, the Hangzhou Asian Games showcased the city’s technological advantage while underscoring its commitment to cultural preservation, ultimately strengthening its global reputation. These findings not only demonstrate a comprehensive understanding of city branding but also provide valuable insights for future large-scale events, suggesting that sports events can serve as essential platforms for city branding and international recognition.